Erratum to: Rock fluidization during peak-ring formation of large impact structures (Nature, (2018), 562, 7728, (511-518), 10.1038/s41586-018-0607-z) - Riller, U.; Poelchau, M.; Rae, A.; Schulte, F.; Collins, G.; Melosh, H.; Grieve, R.; Morgan, J.; Gulick, S.; Lofi, J.; Diaw, A.; McCall, N.; et al. (Nature Publishing Group, 2018)
In this Article, the middle initial of author Kosei E. Yamaguchi (of the IODP–ICDP Expedition 364 Science Party) was missing and his affiliation is to Toho University (not Tohu University). These errors have been corrected online.